2015
DOI: 10.1123/jsep.2015-0166
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Rhythm Neurofeedback Enhances Golf Putting Performance

Abstract: Sensorimotor rhythm (SMR) activity has been related to automaticity during skilled action execution. However, few studies have bridged the causal link between SMR activity and sports performance. This study investigated the effect of SMR neurofeedback training (SMR NFT) on golf putting performance. We hypothesized that preelite golfers would exhibit enhanced putting performance after SMR NFT. Sixteen preelite golfers were recruited and randomly assigned into either an SMR or a control group. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 37 publications
6
83
0
1
Order By: Relevance
“…The results showed that superior shooting performance was related to higher power in 12e15 Hz at the sensorimotor area whereas the neighboring frequency bands remained indifferent. The frequency specificity of the SMR power in skilled motor performance is in agreement with previous studies (Cheng et al, 2015a), which suggests a negative relationship between SMR and the variability in the movement preparation and supports the notion that the sensorimotor cortex may serve as a specific brain area for processing the most relevant cognitive information during air-pistol shooting performance. The finding of no significant cortico-cortical communication between Cz and other electrodes along with the notion that the sensorimotor area is a key region for processing motor interference information (Kober et al, 2015;Sterman, 1996) and pure motor information (Hatfield & Hillman, 2001, pp.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results showed that superior shooting performance was related to higher power in 12e15 Hz at the sensorimotor area whereas the neighboring frequency bands remained indifferent. The frequency specificity of the SMR power in skilled motor performance is in agreement with previous studies (Cheng et al, 2015a), which suggests a negative relationship between SMR and the variability in the movement preparation and supports the notion that the sensorimotor cortex may serve as a specific brain area for processing the most relevant cognitive information during air-pistol shooting performance. The finding of no significant cortico-cortical communication between Cz and other electrodes along with the notion that the sensorimotor area is a key region for processing motor interference information (Kober et al, 2015;Sterman, 1996) and pure motor information (Hatfield & Hillman, 2001, pp.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, neurofeedback training (NFT) aimed at increasing SMR power resulted in improved golf putting performance (Cheng et al, 2015a). The beneficial effects of less variability in the movement preparation by augmented SMR NFT supports previous findings of lower cortical communication between Fz and T3 at high alpha range (Deeny, Hillman, Janelle, & Hatfield, 2003), suggesting more refined processing regarding motor execution.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Adjacent frequency bands can be altered by NFT as well [7]. Cheng et al [5] were able to demonstrate the frequency band specificity of NFT by showing the lack of significant change on flanking frequency bands (theta, alpha, low beta, and high beta) after eight sessions of augmented SMR NFT in a golf putting task. However, the differences in the type of learning, attention, motivation, effort, reinforcement monitoring, etc., which may affect the activity of flanking bands during training.…”
Section: Opinionmentioning
confidence: 99%